PERKAWINAN BEDA AGAMA DI INDONESIA (Studi Putusan 916/Pdt.P/2022/Pn.Sby dan Putusan Nomor 71/Pdt.P/2017/PN Bla) - Rahardian, Alvin; Nurbaedah, Nurbaedah (MIZAN, Jurnal Ilmu Hukum, 2024)
Indonesia as a pluralistic country certainly has many implications, one of which is interfaith marriage, now interfaith marriages are so widespread in Indonesia, one of which is the Surabaya District Court Decision Number 916/Pdt.P/2022/Sby giving permission to the applicants, namely Rizal Adikara and Eka Debora Sidauruk to register their marriage with the population and civil registry office, However, not all applications for interfaith marriages are granted by judges, through decision Number 71/Pdt. The law in Indonesia does not explicitly prohibit interfaith marriages in Indonesia so that judges must explore the values that exist in society, therefore the difference in decisions will be explored regarding the consideration of judges giving different decisions. The purpose of this study is to analyse the validity of interfaith marriages in terms of Islamic law and positive law, to analyse the basis of the Judge's consideration in the birth of the difference in Decision Number 916/Pdt.P/2022/PN.Sby and Decision Number 71/Pdt.P/2017/PN Bla. The research method used is normative. The results of this study are the validity of interfaith marriages according to Islamic law is haram and prohibited, while interfaith marriages according to positive law in Indonesia are carried out through court decision permits and Surabaya district court considerations focus on juridical considerations while the Blora district court considers philosophical values